PENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Marhami, Marhami; Hutabarat, Fahmi Sahab; Muliana, Muliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to examine the mathematical thinking ability between students who are taught with a Realistic Mathematics Education approach and students who are taught with a scientific approach. This research is a quantitative research with a quasi-experimental type and non-equivalent control group design. The population in this study were all students of class XI SMA Negeri 1 Nisam with a sample of two classes, the experimental class which was taught with a Realistic Mathematics Education approach and the control class which was taught with a scientific approach. This sample selection used purposive sampling technique and the instrument used was a test of students' mathematical critical thinking skills. Data analysis used the t-test after the normality test and homogeneity test. The result showed that the significance value of 0.000 was smaller than 0.05, so H0 was rejected, meaning that the mathematical critical thinking skills of students who received Realistic Mathematics Education learning were better than students who received scientific approaches.